Artificial Intelligence in Function of Multimedia Quality for Functional Learning - Hilčenko, Slavoljub; Nikolić, Sanja; Ličina, Boris (Rzeszów University Press, 2025)
Artificial intelligence (AI) is transforming the quality of multimedia content, enabling personalized, interactive, and adaptive learning (AL). This paper explores how AI contributes to improving multimedia materials using methods such as user data analysis, speech synthesis, and image recognition. The focus is on functional learning (FL), where AI enhances student comprehension and engagement. The works of prominent researchers, including Mitchell, Goodfellow, and Russell, are analyzed. The results indicate that AI enhances accessibility, personalization, and efficiency of multimedia educational resources. In addition, recent research 2020–2024 confirms that AI-supported multimedia significantly improves higher-order cognitive processes, problem-solving skills, and learning transfer, which are central components of FL (Zawacki-Richter, Marín, Bond, Gouverneur, 2020; Papamitsiou, Economides, 2021; Holmes, Tuomi, 2022; de Araujo, Dorça, Lima, Fernandes, 2023; Chen, Xie, Zou, 2024).
Keywords: artificial intelligence; multimedia; FL; AL; interactive systems